Anlysis of Sales And Cash Receipt Accounting Information Systems In Efforts To Improve Internal Control (Case Study CV. Andalan Prima) - Hiltia Feni Fitria; Ahmad Sumarlan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This research aims to find out how to apply sales accounting information system analysis and cash receipts in an effort to improve internal control at CV. Prima Mainstay. This sales and cash receipts accounting information system plays a very important role in internal control, if there is no internal system then you cannot monitor the running of a company This research was conducted at CV. Andalan Prima is a distributor that sells various kinds of plastic. This research uses a descriptive qualitative. The data collection techniques in this research are observation, interviews and documentation. Meanwhile, the data analysis technique in this research uses comparative descriptive analysis by describing or illustrating the actual state of the research object. Based on research conducted regarding the sales accounting system at CV. Andalan Prima Bengkulu found that CV. Andalan Prima in its sales activities implements a cash sales system and a credit sales system. Meanwhile, the accounting information system run by the company uses two systems, namely a manual accounting system and a computerized accounting system. The accounting function is separate from the billing function and the cash receipts function.